The trajectory of O Mundo da Saúde Journal in the context of scientific journal - some aspects - Alves Moreno, Leda Virgínia (O Mundo da Saúde, 2007)
The undeniable advance of scientific communication has a direct relation with the changing conditions and dynamic of reality, where scientific journals fulfill a relevant role. In this context, the health field and its complex domain of activity also associate due to the reflexive and critical contribution of O Mundo da Saúde Journal, from the recognition of its 30-year trajectory of scientific production (1977-2007). The present text presents two moments: in the first one, a brief reflection on the importance of scientific journals in the context of scientific production and communication, followed by a moment of presentation of some data referring to the trajectory of O Mundo da Saúde Journal scientific production, based on the issues from January 1977 to January 2007.